ANALISIS SWOT DAYA SAING SEKOLAH: STUDI KASUS DI SEBUAH SMA SWASTA DI KOTA TANGERANG - Nunung Bayu Aji (Universitas Mercu Buana, 2018)
The competitiveness of private schools can be seen from the school accreditation ratings. Private schools that have low accreditation values require strategies to improve their competitiveness. The purpose of this study is to analyze the strategic position of private schools in Tangerang using Strenghts, Weaknesses, Opportunities, and Threats. Data collection was carried out through observation, interviews, study of literature and documents, and questionnaires. Data analysis uses IFAS and EFAS, a SWOT analysis to analyze internal and external factors, Strenghts, Weaknesses, Opportunities, and Threats to obtain a strategic position. The results of the SWOT analysis show that the schools analyzed are in quadrant IV (Weaknesses - Threats), which means the school is in the level of survival. Schools must be able to fix internal weaknesses to avoid and reduce threats. The threat of competition from other schools can be minimized by making unique competition as a differentiator among similar schools.